Analisis Faktor-Faktor yang Mempengaruhi Ketimpangan Distribusi Pendapatan di Propinsi Sumatera Utara - Rahayu, Sri Endang; Febriaty, Hastina (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
After the Covid-19 pandemic, the development process in the economic sector, Indonesia experienced stable and cumulative economic growth of above 5%. Likewise, economic growth in North Sumatra has increased. However, the increasing economic growth has not been accompanied by an even distribution of income in North Sumatra. The main aim of this research is to analyze the factors that influence inequality in income distribution in North Sumatra. This research was conducted in North Sumatra Province using secondary data with a time series from 2010 to 2024, the data was sourced from the North Sumatra Central Statistics Agency. From the results of the research, partially the GRDP and poverty variables have a positive and insignificant effect on the Gini ratio variable. Partially, the TPT variable has a negative and not insignificant effect on the Gini ratio variable. And partially the HDI variable has a positive and significant effect on the Gini ratio variable. Then simultaneously the variables GRDP, TPT, poverty and HDI have a significant effect on the Gini ratio variable.